Controlling the Localization of Liquid Droplets in Polymer Matrices by Evaporative Lithography. Issue 36 (27th July 2016) - Zhao, Huaixia; Xu, Jiajia; Jing, Guangyin; Prieto‐López, Lizbeth Ofelia; Deng, Xu; Cui, Jiaxi
Abstract: Localized inclusions of liquids provide solid materials with many functions, such as self‐healing, secretion, and tunable mechanical properties, in a spatially controlled mode. However, a strategy to control the distribution of liquid droplets in solid matrices directly obtained from a homogeneous solution has not been reported thus far. Herein, we describe an approach to selectively localize liquid droplets in a supramolecular gel directly obtained from its solution by using evaporative lithography. In this process, the formation of droplet‐embedded domains occurs in regions of free evaporation where the non‐volatile liquid is concentrated and undergoes a phase separation to create liquid droplets prior to gelation, while a homogeneous gel matrix is formed in the regions of hindered evaporation. The different regions of a coating with droplet embedment patterns display different secretion abilities, enabling the control of the directional movement of water droplets. Abstract : Evaporative lithography can be used to control the localization of liquid droplets in a silicone‐based polymer matrix. When the solution is placed under a mask, selective solvent evaporation leads to a redistribution of the liquid and polymer components, which results in a patterned film with droplet‐containing and droplet‐free domains.